HUBUNGAN INTENSITAS MENONTON TAYANGAN KEKERASAN DI TELEVISI DENGAN PERILAKU AGRESIF YANG DILAKUKAN ANAK USIA SEKOLAH DI MADRASAH DINIYAH AWALIYAH NURUL HUDA PAJAR BULAN - Riski Amelia; Ruri Fitriyani (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2016)
This study purpose to determine the relationship of the intensity of watching violence on television with aggressive behavior in school-aged children in Madrasah Diniyah Awaliyah Nurul Huda Pajar Bulan. The hyphotesis proposed in this research is there is correlation between intensity of watching violence on television with aggressive behavior in school-aged children in Madrasah Diniyah Awaliyah Nurul Huda Pajar Bulan. The higher the aggressive behavior, and vice versa the lower the intensity of watching violence on television, the lower aggressive behavior. Of subjects used in this study were 70 students/grade III and IV Madrasah Diniyah Nurul Huda Pajar Bulan aged 10-12 years. Data collection using two kinds of scale, the scale of the intensity of watching violence on the television and aggressive behavior scale. Data anayisis methods used in the study is the simple regression analysis. All caunting data analysis was performed using the computer program SPSS version 17. The resuld of the analysis obtained corellation coefisien of R=0,807, P=0,000 means that the hypothesis is accepted